Human amniotic membrane for myocutaneous dehiscence after a radical surgical treatment of vulvar cancer: A case report - Restaino, Stefano; Paparcura, Federico; Giorgiutti, Cristina; Trojan, Diletta; Montagner, Giulia; Pengo, Giancarlo; Pividore, Grazia; Albanese, Roberta; Rampino, Emanuele; Dogareschi, Teresa; Bove, Tiziana; Titone, Francesca; et al. (Frontiers in Oncology, 2022)
Backgroud: the application of the amniotic membrane could have a favourable effect on tissue repair and regeneration. We report the first case of implant of an amniotic membrane in a patient affected by myo-cutaneous dehiscence, after a radical surgical treatment for vulvar cancer. Methods: 74-year-old patient affected by vulvar cancer. After radiotherapy, the patient underwent to an anterior pelvic exenteration with uretero-ileo-cutaneostomy by Wallace, bilateral pelvic lymphadenectomy, omental biopsies, omental flap, bilateral inguinal lymphadenectomy, resection of ulcerated left inguinal lesion, reconstruction with left gracilis muscle flap and locoregional V-Y advancement flap. The patient developed a myo-cutaneous dehiscence. Two months after the surgery, following an accurate curettage of the wound and negative pressure therapy, a patch of human amniotic membrane was implanted. Results: the surgical procedure was easy, feasible and did not require long operating room times. No intraoperative or postoperative complications occurred. The results obtained were encouraging with a marked improvement in the surgical wound. Conclusion: the use of amniotic membranes was safely and easily performed to promote the healing of complicated surgical wounds.